África e o conflito europeu, uma oportunidade perdida? - Almeida, E. C. (Figuras & Negócios, 2023)
Abstract: Brief summary introduction: For around a year and a half, a military – and political – conflict has been going on in Europe, the impacts of which are still, with complete affirmation, far from being properly assessed. Let us remember that in February 2022 the Russian Federation invaded Ukraine in what the Russians expected to be a quick “blitzkrieg” war seeking the Russian leader, Putin, to bring, and make, Ukraine the first effective case of an independent country for the its «living space» (or Lebensraum) by recovering and revitalizing the former territorial space of the Soviet Union Approach to the African position in the face of the Russo-Ukrainian conflict...